2020
DOI: 10.1038/s41387-020-0112-y
|View full text |Cite
|
Sign up to set email alerts
|

The expression signatures in liver and adipose tissue from obese Göttingen Minipigs reveal a predisposition for healthy fat accumulation

Abstract: Background: Model animals are valuable resources for dissecting basic aspects of the regulation of obesity and metabolism. The translatability of results relies on understanding comparative aspects of molecular pathophysiology. Several studies have shown that despite the presence of overt obesity and dyslipidemia in the pig key human pathological hepatic findings such as hepatocellular ballooning and abundant steatosis are lacking in the model. Objectives: The aim of this study was to elucidate why these histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…However, it has also been shown that, in particular, the GM breed is protected against many of the metabolic abnormalities associated with obesity in humans owing to a remarkable ability to expand the adipose compartments to accommodate excess calories, exhibiting a phenotype comparable with the metabolic healthy obese phenotype described in humans (Cirera et al . 2020). Nonetheless, the more relaxed ethical concerns in sampling leptin‐relevant tissues (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been shown that, in particular, the GM breed is protected against many of the metabolic abnormalities associated with obesity in humans owing to a remarkable ability to expand the adipose compartments to accommodate excess calories, exhibiting a phenotype comparable with the metabolic healthy obese phenotype described in humans (Cirera et al . 2020). Nonetheless, the more relaxed ethical concerns in sampling leptin‐relevant tissues (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity triggers low-grade chronic inflammation which can act as risk factor for obesity-related complications, such as NAFLD (Greenberg and Obin, 2006). However, as described in Schumacher-Petersen et al (2019) and Cirera et al (2020), in spite of the metabolic challenges imposed by the FFC diet, hepatic steatosis and other key human pathological findings characterizing NAFLD are lacking in this GM model. The increased inflammation and impaired lipid and cholesterol metabolism resulting from methylation changes observed in this study may have impact on generation of fibrosis in the liver (Chiang et al, 2011;Ahmed et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Parameters with Benjamini-Hochberg corrected P-value <0.05 were considered significant. These baseline, metabolic, and morphometric parameters have been described previously (Andreasen et al, 2018;Schumacher-Petersen et al, 2019;Cirera et al, 2020). with minor modifications.…”
Section: Qpcr Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…We took advantage of a cohort of Göttingen Minipigs being available in conjunction with a larger study. Selected data, including basic characteristics of the Göttingen Minipigs used in this study, have therefore been published previously elsewhere for other scientific purposes [24][25][26][27][28] . One group of minipigs was induced with obesity through a diet-intervention and a subset of the obese minipigs was superimposed with chronic atorvastatin treatment.…”
mentioning
confidence: 99%